An anthropological reflection on the Summer of 2019 and the social movement #Rickyrenuncia (Ricky Resign) in Puerto Rico - Vazquez, Victor Manuel; McAfee, Ashley (Decumanus, 2020)
The following article presents an anthropological and historical analysis based on the social movement referred to as #Rickyrenuncia and its most important achievements during the Summer of 2019 in Puerto Rico. The theoretical concepts used in this analysis are concepts of agency and citizen participation that enabled social mobilization. The subaltern by Gayatri Spivak and the most recent studies regarding Puerto Rico’s political and economic crisis are highlighted in order to contextualize the Summer of 2019.